Paradiplomacy as a Way of Promotion of Regional Identity of the Subjects of Federations - Yury Germanovich Akimov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article is devoted to the international activity of the subjects of federations, to the theoretical approaches to this phenomenon as well as its practical aspects. Special attention is given to the international relations of the subjects with some ethnic and/or linguistic specificity. It analyses the interaction between international activities of such subjects and the promotion of their special regional identity. This phenomenon is described as identifying paradiplomacy. The article deals with its constitutional and legal status, its interconnection with general principles of federalism, specificity of different types of federalism. The examples include the international activity of Quebec, a French-speaking Canadian province, which is one of the most active and visible non-sovereign territorial actors on the world stage for several decades since 1960s till present. It also deals with international activity of the republic of Tatarstan and some other republics of the Russian Federation. The article shows the positive and the negative sides of the identifying paradiplomacy.